Replacement and Urban Identity - Vurucular, Elif (ICONARCH International Congress of Architecture and Planning, 2017)
Cities comprise a multitude of areas, creating history, culture, identity and a sense of urban consciousness, forming their own communities. While a city is built up to fulfil the requirements of urban community, it also engages in continuous renewal due to factors including natural disasters and wars, resulting in demolished and newly constructed buildings. So, over time, urban identities change. Additional factors in the evolution of urban places are the processes of replacement and relocation. Currently, an issue referred to as ‘The Right of Dwelling’ concerning those who have been displaced and relocated as a result of war is receiving insufficient attention. Upon relocation of urban communities, abandoned homes and workplaces remain idle for a period of time, then people from other communities settle in these abandoned places. Consequently, an interruption in the history of urban identity takes place. Especially recently, more and more people have had to abandon their city of residence, even their country, because of conflict. Relocations and population exchanges have taken place during the modern history of the Republic of Turkey. After the Turkish War of Independence, some Greeks in Turkey and Turks remaining in Greece were relocated by government decree and had to leave their residences, forcing people from a different culture and identity to settle in the places left behind by those who were removed. Although the Greeks of Istanbul were not displaced during this period, there was a transformation of their identity in the ensuing years. Greeks and Jews who had been living in the Fener and Balat districts of Istanbul fled in response to the Wealth Tax and upheaval of the 6th and 7th of September, 1955. At the same time, people from other regions of Turkey settled in Fener and Balat, replacing the Greek former residents. So, the city’s cosmopolitan character was further eroded as people of different languages, religions and ethnic identities vanished from the urban landscape. The area’s urban history, which is of replacements and migrations, has resulted in a loss of its former identity, a kind of urban amnesia. It is important that cities are protected as places with values of urban consciousness, culture and history and are prevented from wholesale urban replacement in the pursuit of urban identity. This study discusses the effects of replacement processes resulting from wars and relocations on urban amnesia and identity loss.